Prescribing and up-titration in recently hospitalized heart failure patients attending a disease management program. (1st August 2016) - Carroll, Robert; Mudge, Alison; Suna, Jessica; Denaro, Charles; Atherton, John
Abstract: Background: Heart failure (HF) medications improve clinical outcomes, with optimal doses defined in clinical trials. Patient, provider and system barriers may limit achievement of optimal doses in real life settings, although disease management programs (HF-DMPs) can facilitate up-titration. Methods and results: Secondary analysis of a prospective cohort of 216 participants recently hospitalized with systolic HF, attending 5 HF-DMPs in Queensland, Australia. Medication history at baseline (6 weeks after discharge) and 6 months provided data to describe prescription rates, dosage and optimal titration of HF medications, and associations with patient and system factors were explored. At baseline, 94% were on an angiotensin converting enzyme inhibitor/angiotensin II receptor blocker (ACEI/ARB), 94% on a beta-blocker (BB) and 42% on a mineralocorticoid receptor antagonist (MRA). The proportion of participants on optimal doses of ACEI/ARB increased from 38% (baseline) to 52% (6 months, p = 0.001) and on optimal BB dose from 23% to 49% (p < 0.001). Significant barriers to ACEI/ARB up-titration were body mass index (BMI) < 25, female gender, polypharmacy, previously diagnosed HF, and tertiary hospital. Significant barriers for BB up-titration were BMI < 25, previously diagnosed HF and non-cardiologist care. Conclusions: Effective up-titration in HF DMPs is influenced by patient, disease and service factors. Better understanding of barriers to effective up-titration in women, normal weight, and established HF patients may help provide targeted strategies for improving outcomes in these groups. Highlights: Prescription rates of evidence-based therapy was high in a recently discharged cohort. Most patients were on suboptimal doses of guideline recommended therapy. Significant up-titration of therapies occurred over six months. Barriers to up-titration included normal BMI, female gender, and existing disease. Poorer up-titration in the normal BMI subgroup may contribute to the obesity paradox in HF.